Cold Comfort: Does Chronic Post-Exercise Cold-Water Immersion Blunt Long-Term Training Adaptations? - Bajek, Wiktoria Bajek; Chrzanowski, Dominik; Rymska, Karolina; Lewandowski, Mikołaj; Serafin, Alicja; Kaczmarek, Marcelina; Kuświk, Maciej Krzesimir; Żmuda, Kinga; Andrzejewicz, Jakub; Chlipała, Monika (Quality in Sport, 2026)
Background: High-intensity exercise commonly causes exercise-induced muscle damage (EIMD), neuromuscular fatigue, and delayed-onset muscle soreness (DOMS). While cold-water immersion (CWI) is widely used for recovery, its physiological benefits remain debated. Specifically, the extent to which psychological expectations dictate recovery, and the risk that routine ice baths might interfere with long-term performance gains remain unanswered. Aim: To evaluate the acute and chronic effects of CWI on post-exercise neuromuscular recovery, muscle damage markers, subjective soreness, and long-term training adaptations in active populations. Methods: A literature search was conducted in PubMed (2021–2026). Twelve clinical trials meeting the inclusion criteria were selected and analyzed. Results: CWI did not consistently outperform passive rest or placebo in restoring maximal strength, jump height, or sprint performance following intense exercise. The reduction in DOMS after CWI appeared largely driven by expectancy-based placebo mechanisms rather than physiological tissue repair. However, CWI demonstrated specific benefits, including more effective restoration of parasympathetic autonomic modulation and reduced thermoregulatory stress. Chronic CWI application did not meaningfully alter VO₂max, body composition, or intramuscular adaptive signalling, though repeated exposure elevated heat shock protein-72 (HSP-72) concentrations. Conclusions: Routine CWI offers no clear physiological advantages over passive rest for restoring performance. Perceived recovery benefits appear to be mediated by psychological expectation. Implementation of CWI should therefore be individualised, accounting for the athlete's competitive schedule, personal beliefs, and specific performance objectives.